The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1021/acs.est.1c02649
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection and Electrostatic Recovery of N95 Respirators by Corona Discharge for Safe Reuse

Abstract: With the COVID-19 pandemic surging, the demand for masks is challenging, especially in less-developed areas across the world. Billions of used masks are threatening the environment as a new source of plastic pollution. In this paper, corona discharge (CD) was explored as a safe and reliable method for mask reuse to alleviate the situation. CD can disinfect masks and simultaneously restore electrostatic charges to prevent filtration efficiency deterioration. Electric field, ions, and reactive species generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Corona discharges can be operated in direct current or pulsed mode, where the pointed electrode has a negative or positive potential [ 9 ]. Corona discharges are used in various industrial applications [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Ntp Devices Plasma Composition Biologically Active Agents An...mentioning
confidence: 99%
“…Corona discharges can be operated in direct current or pulsed mode, where the pointed electrode has a negative or positive potential [ 9 ]. Corona discharges are used in various industrial applications [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Ntp Devices Plasma Composition Biologically Active Agents An...mentioning
confidence: 99%
“…Based on our previous results in ref. 25, the discharge voltage and current were respectively set at 25 kV and 0.05 mA, meaning the output power is as low as 1.25 W. The tested surfaces include cloth masks, face shields made of polyethylene terephthalate (PET), coveralls made of polypropylene (PP), alumina, which represents most ceramic surfaces, and stainless steel, which represents conductive surfaces. The specimens were cut into 5 cm by 5 cm squares and then mounted on the ground electrode made from a stainless-steel plate.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous research, we have confirmed the capability of corona discharge (CD) for the safe reuse of N95 respirators by disinfecting and recharging them simultaneously. 25 This technology can address the mask shortage problem and reduce the environmental impact of disposing of used masks. Additionally, we observed cell membrane rupturing and tested DNA damage in the sterilization mechanism of CD.…”
Section: Introductionmentioning
confidence: 99%
“…Airborne particles can be captured by a fiber via four well-known mechanisms: Brownian diffusion, inertial impaction, interception, and electrostatic attraction . In this study, we only focus on the electrostatic attraction for its importance in modern-day filtration media (e.g., N95 respirators and surgical facemasks, which are normally certified using NaCl particles in the size range of 20–500 nm) and as other mechanisms have been studied extensively in past studies. Our study is aimed at calculating the SFE of a bipolarly charged fiber. Only two extreme dipole orientations parallel to the flow and perpendicular to the flow are considered.…”
Section: Methodsmentioning
confidence: 99%
“…Here, Kn f = 2λ/ d f is the fiber Knudson number and d f and λ are the fiber diameter and the MFP of the air molecules, respectively. Most facemasks and respirators (e.g., N95 masks) are made of melt-blown and spun-bond fibers with a diameter in the range of 4–16 μm. , With fibers ranging from 4 to 16 μm in diameter and λ = 65 nm in atmospheric conditions, the slip flow regime is expected to prevail in the flow domain. Therefore, the aerodynamic slip at the fiber surface was incorporated in our simulations by means of a user-defined function (UDF) (see refs for more details).…”
Section: Methodsmentioning
confidence: 99%